2019
DOI: 10.1590/s1677-5538.ibju.2018.0276
|View full text |Cite
|
Sign up to set email alerts
|

The effect of urethroplasty surgery on erectile and orgasmic functions: a prospective study

Abstract: Objectives: to examine the effects of urethroplasty surgery on sexual functions by taking into account age, location of stenosis, length of stenosis and surgical technique parameters. Materials and Methods: The prospective study was conducted between January 2015 and August 2017 with 60 cases. Patients were categorized according to age groups (19-65 / 65-75 years), surgery technique and stricture localization and length. Before the urethroplasty operation and postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
(26 reference statements)
1
2
0
6
Order By: Relevance
“…Even though we found that urethroplasty operation alone did not affect erectile and orgasmic function in a study of 60 patients in 2019, there are contradictory publications in the literature [22,23]. Regarding sexual complications, age of the patient, surgery type and the cause for stricture has been stated as more influencing factors than the characteristics of the stricture [22,24,25]. Overall, complications rates of this study were found to be compatible with the literature.…”
Section: Discussionsupporting
confidence: 86%
“…Even though we found that urethroplasty operation alone did not affect erectile and orgasmic function in a study of 60 patients in 2019, there are contradictory publications in the literature [22,23]. Regarding sexual complications, age of the patient, surgery type and the cause for stricture has been stated as more influencing factors than the characteristics of the stricture [22,24,25]. Overall, complications rates of this study were found to be compatible with the literature.…”
Section: Discussionsupporting
confidence: 86%
“…В метаанализ были включены 16 научных работ [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] c общим числом пациентов 1476 (см. таблицу).…”
Section: результатыunclassified
“…Схожие результаты были получены и в исследовании, проведенном A. Urkmez и соавт. При сравнении результатов внутри групп до 65 и старше 65 лет статистически значимой разницы не получено, однако при сопоставлении результатов между возрастными группами у пациентов младше 65 лет показатели эректильной функции были статистически значимо выше (p = 0,000) [22]. Роль возраста пациентов также была отмечена в исследовании U.P.…”
Section: результатыunclassified
See 1 more Smart Citation
“…The authors are to be commended for performing this study examining the impact of urethroplasty on EF specifically, but should acknowledge that the sample size is small and only a single questionnaire was used to assess EF. Urkmez et al [8] in 2019 published a series of 60 patients who underwent substitution or anastomotic urethroplasty and reported no impact on EF or orgasmic function, but acknowledged the lack of validated questionnaires available to assess sexual function after urethroplasty.…”
mentioning
confidence: 99%